2019
DOI: 10.1007/s11676-019-01019-3
|View full text |Cite
|
Sign up to set email alerts
|

Past, present and future of industrial plantation forestry and implication on future timber harvesting technology

Abstract: Plantation forests are established, and expanding, to satisfy increasing global demand for timber products. Shifting societal values, such as safety, productivity, environmental, quality and social are influencing the plantation forestry sector. This is primarily driven through an ever increasing world population, which in turn influences the way nations view the value systems by which they live. More people require more resources-also forest products. Also, the availability of information is influencing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(57 citation statements)
references
References 101 publications
4
52
0
1
Order By: Relevance
“…Our finding of a positive effect of elevation on C d in all ecoregions of Northeast Asia, consistent with two recent studies (Wang et al, 2008(Wang et al, , 2018, can be attributed to the fact that high-elevation mountainous regions are relatively less affected by historical logging than the low elevation plains (Tang et al, 2006) due to excessive slope gradient and small compartment surface (McEwan et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of a positive effect of elevation on C d in all ecoregions of Northeast Asia, consistent with two recent studies (Wang et al, 2008(Wang et al, , 2018, can be attributed to the fact that high-elevation mountainous regions are relatively less affected by historical logging than the low elevation plains (Tang et al, 2006) due to excessive slope gradient and small compartment surface (McEwan et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a positive effect of elevation on C d in all ecoregions of Northeast Asia, consistent with two recent studies (Wang et al., 2008, 2018), can be attributed to the fact that high‐elevation mountainous regions are relatively less affected by historical logging than the low elevation plains (Tang et al., 2006) due to excessive slope gradient and small compartment surface (McEwan et al., 2020). Meanwhile, our finding of a positive effect of human footprint ( H 1 ) on C d in all ecoregions but Eco5 (Figure 8) indicates that the influence of human interference on forest biomass C stock can go both ways.…”
Section: Discussionsupporting
confidence: 91%
“…The role of plantations as only being a source of roundwood for global markets has started changing. The future demand for forest products will most likely be met by plantations that have good conservation and biodiversity standards, as well as respecting the needs and livelihoods of local communities (Innes 2013; McEwan et al, 2020 , Szulecka et al, 2014 ).…”
Section: Investment Science Historymentioning
confidence: 99%
“…An increasing number of plantations have been established in recent years to satisfy the increasing global demand for timber products (FAO 2005). As one of the forestry practices that increases productivity, intensive management (IM) is essential for meeting current and future timber needs (McEwan et al 2020). Several studies have shown that IM significantly increases CO 2 emissions (Mori et al 2017;Yang et al 2017) but does not affect CH 4 or N 2 O emissions from forest soils (Mori et al 2017).…”
Section: Introductionmentioning
confidence: 99%